Pengembangan Model Gaya Kepemimpinan Situasional Kepala Balai Penyuluhan Pertanian di Provinsi Kalimantan Selatan - Suprijanto Suprijanto; Abdussamad Abdussamad; Masyhudah Rosni (AGRIDES: Jurnal Agribisnis Perdesaan, 2011)
The objective of research was to develop situational leadership style model of Head of Agricultural Extension Office (AEO) in South Kalimantan Province. Research method used was survey method, which was complemented by questionnaire of LEAD (Leader Effectiveness and Adaptability Description) and maturation level. The LEAD was developed by Hersey and Blanchard in 1965 (Bruno & Lay, 2006).  This questionnaire had been filled by AEO Head and Staff to assess Staff level of maturation. Respondents were selected by using multiple-stage sampling method. To know the efeectiveness of development of AEO Head situational leadership style, had been done experiment with design of randomized pretest-posttest control group design and t-test at the 0,05 level of significance had been used. Based on the data analyses, the conclusions could be drawn were as follows: Of 222 AEO Staff, it was found that 18 persons (53%) had maturation level of M3 (moderate to high); 73 persons (33%) had maturation level of M2 (low to moderate); 28 persons (13%) had maturation level of M4 (high), and only 3 persons (1%) who had maturation level of M1 (low) . By the differences of the gap between posttest-pretest scores on experimental group and on control group, it can be said that the development of situational leadership style model was included in effective category.